3D Finite Element Analysis of milling process for non-ferrous metal using deform-3D. (2020) - Vishwakarma, Premnarayan; Sharma, Ajay
Abstract: Milling is one of the most important conventional machining operations used in Industry. The milling operation is influenced by many parameters. This paper deals with the acquirement and comparison of surface roughness values obtained during milling operation done on aluminum with the simulated values through FEA. The material was chosen bacause of its importance in industry and its susceptibility to degradation through surface. The parameter chosen were speed, feed and depth of cut. Material selected for the tool is carbide (15% cobalt), having tensile strength of about 400 N/mm 2 . Finite Element Analysis using DEFORM 3D software is done on the milling operation by varying the parameters of mill cutter on the work piece, roughness values are obtained during each individual process. The material is defined in software by using John-cook's equation. The same procedure is done in real time for the same processing conditions used in software on a CNC vertical milling machine.